1992
DOI: 10.1093/protein/5.4.295
|View full text |Cite
|
Sign up to set email alerts
|

Main structural and functional features of the basic cytosolic bovine 21 kDa protein delineated through Hydrophobic Cluster Analysis and molecular modelling

Abstract: A 21 kDa protein purified from bovine brain cytosol was previously described as a hydrophobic ligand binding protein; however, its accurate biological function remained still uncertain. In order to get further information about its potential biological role, an extended prediction of its secondary and three dimensional structures was undertaken. We describe here a process which permitted us to discover a structural homology between the 21 kDa protein and the N-domain of yeast phosphoglycerate kinase (PGK). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…We recently reported that the amino-acid sequences of rat and human HCNP-precursor proteins, deduced from the respective cDNAs , were highly homologous with those of the bovine phosphatidylethanolamine-binding protein (Schoentgen et al, 1987) and the rat brain 23-kDa protein associated with opioid pep-consensus sequence for an ATP binding site (Schoentgen et al, 1992;Tohdoh et al, 1995), and we have shown that the precursor proteins of murine and human origin do indeed bind ATP .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…We recently reported that the amino-acid sequences of rat and human HCNP-precursor proteins, deduced from the respective cDNAs , were highly homologous with those of the bovine phosphatidylethanolamine-binding protein (Schoentgen et al, 1987) and the rat brain 23-kDa protein associated with opioid pep-consensus sequence for an ATP binding site (Schoentgen et al, 1992;Tohdoh et al, 1995), and we have shown that the precursor proteins of murine and human origin do indeed bind ATP .…”
Section: Discussionmentioning
confidence: 86%
“…, 1987), and is indistinguishable from the partial sequence of a 23-kDa plasma membrane protein from rat sperm (Jones and Hall, 1991), as well as from a rat 23-kDa protein associated with an opioid peptide (Grandy et al, 1990). Moreover, it has been suggested that the phosphatidylethanolamine-binding protein has a consensus sequence of an ATP-binding site (Schoentgen et al, 1992), and we found that the HCNPprecursor proteins of rats and humans also contain such a motif, and that both have a specific affinity for ATP, but not for any other nucleotide . In more recent studies in which a radioimmunoassay (RIA) and a combination of RIA and high-pressure liquid chromatography were used, we demonstrated the presence of HCNP and its precursor protein in a variety of rat tissues, with amounts in neuronal tissues examined inversely related to age of the animal .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the building of a 21-kDa model was carried out from the crystallographic data of the Saccharomyces cerevisiae phosphoglycerate kinase. The model revealed a potential nucleotide binding site which was confirmed by biochemical tests, suggesting that the 21-kDa protein may be involved in phosphorylation or modulation mechanisms (Schoentgen et al 1992). More recently, Grandy et al (1990) isolated a 23-kDa protein from R. norvegicus brain membranes and established the sequence of a cDNA encoding this protein.…”
Section: Introductionmentioning
confidence: 76%
“…Furthermore, when comparing the amino acid sequences of the 21 23 kDa protein family members, the central region constituted by residues 60 126 appeared to be particularly well conserved (see Fig. 1); interestingly, this central region corresponds to the potential nucleotide binding site observed in the bovine protein model [18]. The nucleotide site may be implicated in the binding of the bovine brain 21 23 kDa protein to small GTP-binding proteins [19]; the possibility for the mammalian protein to bind small G proteins is in accordance with the observation that TFS1 seems to be implicated in pathway modulations involving small GTPbinding proteins.…”
Section: Potential Biological Roles Of the 21-23 Kda Protein Familymentioning
confidence: 92%
“…Based on this result, a molecular model of the bovine 21-23 kDa protein was built from the crystallographic data of the Saccharomyces cerevisiae phosphoglycerate kinase. This model contained a consensus sequence and three-dimensional folding corresponding to a potential nucleotide binding site [18]. The binding of nucleotides (especially FMN and GTP) to the bovine brain 21-23 kDa protein was then demonstrated by affinity chromatography [19].…”
Section: Structural Features Of the 21-23 Kda Protein From Mammalian mentioning
confidence: 99%